Memahami Komunikasi Kelompok dalam Pendampingan Korban Kekerasan Jerbasis Gender - Setiawan, Yuliyanto Budi (Jurnal The Messenger, 2009)
Through this study, some topics/themes  which where ever communicated by participants together in a meeting of Support Group, among others violence cases experienced by each member/victim, the form of gender emancipation and anti-' trafficking. The obstacles experienced by a member when her violence case was being handled by the police,  a  discussion of the adaptation of Support Group with its surrounding environment, felt by the victim,  discussion of business development of the member, the distribution of petrol fund from the Semarang City Government for the unable community as well as discussions on the content of UP-PKDRT No.23/2004. Counselor/Facilitator was noted to use the method of Art Therapy and Method of Discussion during facilitating victims in the mentioned therapy group.